Bone mineral density and body composition of the United States Olympic women's field hockey team - Sparling, P. B.; Snow, T. K.; Rosskopf, L. B.; O'Donnell, E. M.; Freedson, P. S.; Byrnes, W. C. (British Journal of Sports Medicine, 1998)
OBJECTIVE: To evaluate total bone mineral density (BMD) and body composition (% fat) in world class women field hockey players, members of the 1996 United States Olympic team. METHODS: Whole body BMD (g/cm2) and relative body fatness (% fat) were assessed by dual energy x ray absorptiometry using a Lunar DPX-L unit with software version 1.3z. Body composition was also estimated by hydrostatic weighing and the sum of seven skinfolds. Results: Mean (SD) BMD was 1.253 (0.048) g/cm2 which is 113.2 (4.0)% of age and weight adjusted norms. Estimates of body composition from the three methods were similar (statistically non-significant): 16.1 (4.4)% fat from dual energy x ray absorptiometry, 17.6 (3.2)% from hydrostatic weighing, and 16.9 (2.6)% from the sum of seven skinfolds. Mean fat free mass was approximately 50 kg. CONCLUSIONS: The mean whole body BMD value for members of the 1996 United States Olympic women's field hockey team is one of the highest reported for any women's sports team. Moreover, the mean fat free mass per unit height was quite high and % fat was low. In this group of world class sportswomen, low % fat was not associated with low BMD.